2010
DOI: 10.3233/ch-2009-1251
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte aggregation at non-steady flow conditions: A comparison of characteristics measured with electrorheology and image analysis

Abstract: In the present study electro-rheology (Contraves LS30 viscometer-based system) and optical shearing microscopy (Lincam CSS450 system and image analysis) techniques have been utilized in order to provide quantitative data on the behaviour of the microstructural properties of whole normal human blood at non-steady flow conditions. The objective of this work is to contribute towards a better understanding of red blood cell aggregation at flow conditions similar to that occurring in a circulatory system and to aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Erythrocyte aggregation at non-steady flow conditions in the Couette rheometric cell has been studied by Kaliviotis et al [ 21 ]. Electro-rheology was applied in parallel with optical shearing technique to study blood microstructural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocyte aggregation at non-steady flow conditions in the Couette rheometric cell has been studied by Kaliviotis et al [ 21 ]. Electro-rheology was applied in parallel with optical shearing technique to study blood microstructural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A H-shaped microfluidic device, composed of two parallel side channels and a bridge channel, can effectively measure blood viscosity under various flow conditions 13 . RBC aggregation can be measured directly (microscopic observation methods) 14 15 , or indirectly. The latter includes measurement modalities such as erythrocyte sedimentation rate 16 , light reflection or transmission 17 , ultrasonic 18 19 and electrorheological methods 20 .…”
mentioning
confidence: 99%
“…To this extent the technique used for the development of the aggregation and integrity indices (equations 1 and 2) has been compared to other techniques and has been concluded that it can reveal features of blood microstructure identical to those obtained by other optical and electrorheology techniques [21,23,24]. In addition, direct comparison of data from optical shearing microscopy with results obtained from electrorheology techniques at identical flow conditions, but in different gaps (30 and 1000 m in optical microscopy and electrorheology respectively) have shown that there is an excellent agreement between the techniques for certain flow conditions, whereas discrepancies appear in the measurement with excessive aggregation [25].…”
Section: Discussionmentioning
confidence: 69%